KISSING STENT TECHNIQUE IN THE TREATMENT OF INNOMINATE ARTERY STENOSIS - Camacho, Nelson (2017)
Introduction: The presence of symptomatic atherosclerotic stenosis of the innominate artery is an uncommon condition. The authors report the use of kissing stent technique in right subclavian and common carotid arteries with covered stents and cerebral protection by direct clamping of common carotid artery, as a hybrid endovascular alternative to treat symptomatic stenosis of the innominate artery. Case Report: A 75-year-old male was admitted to Vascular Surgery Department with repeated transient ischemic attacks (TIA’s) of the right cerebral hemisphere, resulting in transitory left hemiparesis. Computerized tomography angiography (CTA) excluded significant carotid lesions and revealed stenosis of the innominate artery associated with mural thrombus that extended to the bifurcation. The right common carotid artery and axillary artery were surgically exposed. Brain protection was achieved by direct clamping of the common carotid artery and subsequently carotid and axillary retrograde endovascular access was obtained. Two balloon-expandable covered stents were placed in the innominate, subclavian and right common carotid arteries, using the kissing stent technique. At the end of the procedure, a good permeability of the revascularized arteries was verified and a direct expulsion of eventual embolic material was performed prior to declamping. The postoperative period was uneventful. Conclusion: The kissing stent technique, with covered stents, in innominate, right subclavian and common carotid arteries with direct protection of the common carotid by clamping is a possible and minimally invasive solution for the treatment of symptomatic stenosis of the innominate artery.